Residential Space Poverty and the Spatial Solutions for Chinese Migrants in Hong Kong. Issue 2 (3rd April 2022) - Wang, Yuxuan; Lo, Alex Y.
ABSTRACT: Residential space poverty has been a recurring urban phenomenon. This study shows how new migrants in Hong Kong navigate residential space poverty. We used Q-method to understand the subjective experiences of new migrants living in poor informal housing units. These migrants indicate mixed subjective experiences in using public and openly accessible spaces. Some of these spaces act as a "third place" that improves migrants' quality of life, but some socio-economic factors have undermined their role as a spatial solution. Although these spaces can contribute to social vulnerability reduction and social integration, their benefits for the most disadvantaged groups are unclear.